Evaluation of PCR Primer Selectivity and Phylogenetic Specificity by Using Amplification of 16S rRNA Genes from Betaproteobacterial Ammonia-Oxidizing Bacteria in Environmental Samples - Junier, Pilar; Kim, Ok-Sun; Hadas, Ora; Imhoff, Johannes F; Witzel, Karl-Paul (My University, 2008)
The effect of primer specificity for studying the diversity of ammonia-oxidizing betaproteobacteria (βAOB) was evaluated. βAOB represent a group of phylogenetically related organisms for which the 16S rRNA gene approach is especially suitable. We used experimental comparisons of primer performance with water samples, together with an in silico analysis of published sequences and a literature review of clone libraries made with four specific PCR primers for the βAOB 16S rRNA gene. With four aquatic samples, the primers NitA/NitB produced the highest frequency of ammonia-oxidizing-bacterium-like sequences compared to clone libraries with products amplified with the primer combinations βAMOf/βAMOr, βAMOf/Nso1255g, and NitA/Nso1225g. Both the experimental examination of ammonia-oxidizing-bacterium-specific 16S rRNA gene primers and the literature search showed that neither specificity nor sensitivity of primer combinations can be evaluated reliably only by sequence comparison. Apparently, the combination of sequence comparison and experimental data is the best approach to detect possible biases of PCR primers. Although this study focused on βAOB, the results presented here more generally exemplify the importance of primer selection and potential primer bias when analyzing microbial communities in environmental samples.